Carbon incentives and farm economics : A study of peatland drainage optimization - Rämö, Janne; Tzemi, Domna; Miettinen, Antti; Wejberg, Henrik; Lehtonen, Heikki (Elsevier, 2025)
Natural, waterlogged peatlands are recognized as the most efficient carbon storage ecosystems, playing a critical role in climate regulation. However, in Europe, agriculture on drained peat soils — although comprising only 2.5 % of the agricultural area — contributes disproportionately, generating approximately 25 % of the EU’s total agricultural greenhouse gas emissions. This study examines the potential of drainage optimization and rewetting as strategies to reduce emissions from peatlands while balancing agricultural productivity. We quantitatively analyse the production, land use, and economic implications for farmers in two different farm scenarios using economic modelling and dynamic optimization. Our analysis evaluates the impact of carbon subsidy pricing on crop diversity and farmer income. Results indicate that while carbon subsidy prices have minimal influence on crop rotation diversity, they significantly affect farmers' income. With a subsidy price of 30€ per ton of CO2 equivalent, or 80€ per ton in the case of high-value crops, farmers transition into "carbon farmers", obtaining higher share of total net present value from carbon subsidies rather than traditional agricultural income. Furthermore, the majority of climate benefits, including GHG reduction, are realized already at the 30€/tCO2e subsidy threshold. The findings suggest that carbon subsidies could offer a viable financial incentive for farmers to adopt peatland rewetting practices, which could reduce GHG emissions substantially. However, subsidy designs need careful calibration to ensure they do not distort agricultural practices or reduce crop diversity, while still delivering significant climate benefits.
Keywords: agricultural economics; peatland agriculture; greenhouse gases; crop cultivation